The use of a Giardia vaccine as an immunotherapeutic agent in dogs. - Olson, M E (2001)
Dogs (n = 13), which had failed to be cured of giardiosis following chemotherapeutic measures, were treated with a Giardia vaccine (2-3 injections). Clinical signs resolved between 16 and 42 days postvaccination and cessation of fecal cyst shedding was between 21 and 70 days. Vaccination is a potential method of treating giardiosis in dogs.